THE EFFECT OF SALES GROWTH, CAPITAL INTENSITY AND LEVERAGE ON TAX AVOIDANCE - Yasmin, Ayu Octaviana; Fitriyah, Fitriyah (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
This study investigates the impact of Sales Growth, Capital Intensity, and Leverage on Tax Avoidance within consumer goods industry sector companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2022. Employing a quantitative approach, the study uses purposive sampling to select 16 companies over a 5-year period, resulting in 80 samples that meet specified criteria. Financial statement data form the basis of the analysis, which incorporates descriptive statistical tests, regression model selection, panel data estimation techniques, classical assumption tests, panel data regression tests, determination coefficient tests, and hypothesis testing. The E-Views 9 application facilitated the data analysis. Findings from the F statistical test indicate that Sales Growth, Capital Intensity, and Leverage together influence Tax Avoidance. Furthermore, the t statistical test reveals that while Sales Growth positively impacts Tax Avoidance, Capital Intensity and Leverage do not have a significant effect.